2019
DOI: 10.1002/pbc.27667
|View full text |Cite
|
Sign up to set email alerts
|

Low‐risk factors for severe bacterial infection and acute chest syndrome in children with sickle cell disease

Abstract: Introduction The rate of bacterial infections in children with sickle cell disease (SCD) has decreased in recent years, mainly due to penicillin prophylaxis and vaccination. Objectives To determine the rate of severe bacterial infection (SBI) in a cohort of children with SCD and to describe low‐risk factors for confirmed SBI (CSBI) and acute chest syndrome (ACS). Methods This 11‐year retrospective cohort study included children with febrile SCD admitted to a reference hospital in Spain. A case‐control study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…Despite the low proportion of con rmed SBI in this cohort, almost all patients received at least one dose of antibiotic (96.2%), in agreement to current guidelines [18][19][20].This high use of antibiotics emphasizes the importance of de ning laboratory parameters that could early discriminate the etiology of fever in these patients, in order to optimize the antimicrobial prescription. Children with SBI presented more frequently with hemodynamic instability and had higher in ammatory parameters (neutrophils, CRP and procalcitonin) than the rest of the patients, similarly to what was described in other studies [1,[5][6][7][8][9]. We also found that children with SBI had signi cantly higher IL-6 levels when compared with those with VI, NPI and controls, with the highest value observed in the only patient with con rmed pneumococcal pneumonia.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the low proportion of con rmed SBI in this cohort, almost all patients received at least one dose of antibiotic (96.2%), in agreement to current guidelines [18][19][20].This high use of antibiotics emphasizes the importance of de ning laboratory parameters that could early discriminate the etiology of fever in these patients, in order to optimize the antimicrobial prescription. Children with SBI presented more frequently with hemodynamic instability and had higher in ammatory parameters (neutrophils, CRP and procalcitonin) than the rest of the patients, similarly to what was described in other studies [1,[5][6][7][8][9]. We also found that children with SBI had signi cantly higher IL-6 levels when compared with those with VI, NPI and controls, with the highest value observed in the only patient with con rmed pneumococcal pneumonia.…”
Section: Discussionsupporting
confidence: 89%
“…The [58][59][60][61][62][63][64][65][66]. Prospective cohort studies of SCD patients are rare in Africa due to barriers to medical monitoring [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using different cut-off levels [13][14][15][16] with a high negative predictive value reported elevated procalcitonin as a marker of severe bacterial infection in patients with SCD and vaso-occlusive crisis. Our results are in accordance with trials performed either in emergency departments [9,[17][18][19] or in primary care [20] to reduce antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Possible or proven lung infection was diagnosed during 13% of all ACS episodes. The number of days alive without antibiotics at Day 21 was higher during the intervention phase: 15 [14][15][16][17][18] vs. 13 [13,14] days (p = 0.001). More patients had a short (≤3 days) antibiotic course during intervention phase: 31% vs 9% (p = 0.01).…”
mentioning
confidence: 99%